Dampak Pandemi Covid 19 terhadap Kepatuhan Ibu Melakukan Kunjungan Kehamilan - Iin Octaviana Hutagaol; Arini Arini; Cicik Mujianti Mujianti (Sarana Ilmu Indonesia (salnesia), 2021)
Maternal and neonatal services have not escaped the impact of the Covid 19 pandemic. It can indirectly increase the return of mortality and morbidity to both mother and baby. This study aims to assess the impact of the Covid 19 pandemic on the compliance of pregnant women to revisit antenatal care. The sampling technique used in this study was stratified random sampling, using the Lemeshow formula with a sample count of 126 people with the inclusion criteria set by the researcher. The design of this study was analytic observational. Data collection was carried out through observation questionnaire sheets that were collected offline and online (Google Form). The test used in this study was Mann Whitney. The results of the analysis show that the significance value is 0.003 at the 2nd-trimester pregnancy visit and 0.001 at the 3rd-trimester pregnancy visit, therefore, statistically p <0.05 there is a relationship between the impact of the pandemic and the 2nd and 3rd-trimester pregnancy visits. Mann Whitney with a higher ranking ratio (mean) between the affected groups (66.92) and those not affected (41.59). Thus, s who were affected by the pandemic were economically more likely to not attend pregnancy visits compared to those who were not economically affected by the pandemic. The results of the study show that there is a relationship between the impact of the COVID-19 pandemic and the unity of mothers carrying out pregnancy visits during the pandemic, this is due to government policies to limit and also anxiety of pregnant women.